Community risk factors for ocular Chlamydia infection in Niger: pre-treatment results from a cluster-randomized trachoma trial. - Abdou Amza; Boubacar Kadri; Baido Nassirou; Nicole E Stoller; Sun N Yu; Zhaoxia Zhou; Stephanie Chin; Sheila K West; Robin L Bailey; David C W Mabey; Jeremy D Keenan; Travis C Porco; et al. (Public Library of Science (PLoS), 2012)
Trachoma control programs utilize mass azithromycin distributions to treat ocular Chlamydia trachomatis as part of an effort to eliminate this disease world-wide. But it remains unclear what the community-level risk factors are for infection.This cluster-randomized, controlled trial entered 48 randomly selected communities in a 2×2 factorial design evaluating the effect of different treatment frequencies and treatment coverage levels. A pretreatment census and examination established the prevalence of risk factors for clinical trachoma and ocular chlamydia infection including years of education of household head, distance to primary water source, presence of household latrine, and facial cleanliness (ocular discharge, nasal discharge, and presence of facial flies). Univariate and multivariate associations were tested using linear regression and Bayes model averaging.There were a total of 24,536 participants (4,484 children aged 0-5 years) in 6,235 households in the study. Before treatment in May to July 2010, the community-level prevalence of active trachoma (TF or TI utilizing the World Health Organization [WHO] grading system) was 26.0% (95% CI: 21.9% to 30.0%) and the mean community-level prevalence of chlamydia infection by Amplicor PCR was 20.7% (95% CI: 16.5% to 24.9%) in children aged 0-5 years. Univariate analysis showed that nasal discharge (0.29, 95% CI: 0.04 to 0.54; P = 0.03), presence of flies on the face (0.40, 95% CI: 0.17 to 0.64; P = 0.001), and years of formal education completed by the head of household (0.07, 95% CI: 0.07 to 0.13; P = 0.03) were independent risk factors for chlamydia infection. In multivariate analysis, facial flies (0.26, 95% CI: 0.02 to 0.49; P = 0.03) and years of formal education completed by the head of household (0.06, 95% CI: 0.008 to 0.11; P = 0.02) were associated risk factors for ocular chlamydial infection.We have found that the presence of facial flies and years of education of the head of the household are risk factors for chlamydia infection when the analysis is done at the community level.ClinicalTrials.gov NCT00792922.